On invariant measures for ℬ‐free systems. Issue 6 (20th April 2015) - Kułaga‐Przymus, Joanna; Lemańczyk, Mariusz; Weiss, Benjamin
Abstract : We show that theB ‐free subshift( S, X B ) associated to aB ‐free system is intrinsically ergodic, that is, it has exactly one measure of maximal entropy. Moreover, we study invariant measures for such systems. It is proved that each ergodic invariant measure is of joining type, determined by a joining of the Mirsky measure of aB ' ‐free subshift contained in( S, X B ) and an ergodic invariant measure of the full shift on 0, 1 Z . Moreover, each ergodic joining type measure yields a measure‐theoretic dynamical system with infinite rational part of the spectrum corresponding to the above Mirsky measure. Finally, we show that, in general, hereditary systems may not be intrinsically ergodic.